NEUROLOGIC MANIFESTATIONS ASSOCIATED WITH COVID-19 IN PEDIATRIC PATIENTS AT DR. KARIADI HOSPITAL SEMARANG - Sareharto, Tun Paksi; Dania Emeralda Firdausy; Santoso Jaeri; Alifiani Hikmah Putranti (Faculty of Medicine Universitas Kristen Duta Wacana, 2024)
Background: Coronavirus Disease-19 (COVID-19), a severe acute respiratory syndrome, stems from a novel coronavirus known as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The common symptoms and signs of COVID-19 are fever, cough, diarrhea, and myalgia as well as neurological manifestations. Neurological manifestations of COVID-19 in adult patients have been well recognized, unfortunately, there is limited evidence of neurological manifestations of COVID-19 in children, especially in Indonesia, so herewith we describe neurological manifestations in children, to contribute to the knowledge in the fields of pediatric health and neurology, particularly their correlation with COVID-19. Objective: To determine the neurological manifestations in children with COVID-19. Method: An observational analytic study among 124 pediatric patients with COVID-19 at Dr. Kariadi Hospital Semarang. Demographic and clinical data were obtained from medical records. To determine risk factors for the occurrence of neurological manifestation, the chi-square test, Fisher exact test, and Mann-Whitney U-test were performed. Results: Out of 124 subjects, 49 (39.5%) developed neurological manifestations, including headache (10%), seizure (23%), weakness (5%), dizziness (0.8%), vision impairment (0.8%), ataxia (0.8%), coma (11.3%), paresthesia (0.8%), acute encephalopathy (3.2%), sympathetic storming (0.8%), and others (9.7%). Diagnosis of Multisystem Inflammatory Syndrome in Children (MIS-C) was found in 10 (8.1%) patients, in addition, there was a significant association between the diagnosis of MIS-C, comorbid conditions, and outcomes among patients and neurological manifestations. Conclusion: The most common neurological manifestation experienced by pediatric patients with COVID-19 in this study was seizures. Patients with MIS-C and pre-existing conditions are at higher risk of experiencing neurological manifestations. Children with neurological manifestations more frequently presented with worse outcomes.